2016
DOI: 10.5897/ajb2015.14676
|View full text |Cite
|
Sign up to set email alerts
|

Physico chemical evaluation of coffee husk, wastes of enset (Enset ventricosum), vegetable and khat (Catha edulis) through vermicomposting employing an epigeic earthworm Dendrobaena veneta (Rosa, 1886)

Abstract: The major objective of this 90 days vermicomposting work was to evaluate the performance of epigeic earthworms, Dendrobaena veneta, to alter and change four commonly dumped and littered solid wastes in Ethiopian cities and towns into a high quality vermicompost. The experiments were conducted in cylindrical plastic containers with 26 cm depth and 53 cm width under shade. All containers were perforated on the sides for aeration as well as bottom for leachate drainage purpose. The wastes were mixed with cow dung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The selection of these organic wastes was based on the large accumulation and great potential in the study area. Vermicomposts with a mixture of 75% coffee pulp and 25% cow dung [ 19 ] were prepared in 2 m × 1 m × 1 m boxes and cocomposted for thirty days, to break down the substrates into smaller parts that are more easily appetizing to vermin worms. Both Eisenia fetida and Dendrobaena veneta adult earthworm species were introduced into the vermicomposting boxes after cocomposting mixed materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of these organic wastes was based on the large accumulation and great potential in the study area. Vermicomposts with a mixture of 75% coffee pulp and 25% cow dung [ 19 ] were prepared in 2 m × 1 m × 1 m boxes and cocomposted for thirty days, to break down the substrates into smaller parts that are more easily appetizing to vermin worms. Both Eisenia fetida and Dendrobaena veneta adult earthworm species were introduced into the vermicomposting boxes after cocomposting mixed materials.…”
Section: Methodsmentioning
confidence: 99%
“…Both Eisenia fetida and Dendrobaena veneta adult earthworm species were introduced into the vermicomposting boxes after cocomposting mixed materials. Vermicompost was produced and harvested after thirty days by following the recommended procedures and appropriate media [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that earthworms can process household garbage, city, refuge, sewage sludge and industrial (paper, wool, food) wastes (Hartenstein, 1979;Appelhof, 1980;Senapati and Dash, 1982). A number of researchers have investigated the capability of earthworms as a treatment or management factor for numerous organic waste streams (Chauhan et al, 2010;Kalamdhad and Khwairakpam, 2012;Mehta and Karnwal, 2013;Dandotiya and Agrawal, 2014;Degefe et al, 2016). Earthworms work upon sewage sludge and solids from water wastes (Sinha et al, 2010), processed paper industry waste (Butt, 1993), brewery waste (Butt, 1993), and coffee pulp.…”
Section: Significance Of Earthworms In Waste Managementmentioning
confidence: 99%
“…Recent case studies (Franca and Oliveira 2009;Kassa et al 2011;De Rezende et al 2012;Shemekite et al 2014;Degefe et al 2016) reported composting of coffee husk with cow dung, fruits/vegetables, effective microorganisms and Khat (Catha edulis). However, no research was carried out to investigate the composting and co-composting of coffee husk and pulp with source-separated municipal solid waste including the leaves of false banana (Ensete ventricosum), fruits, vegetables, khat/Catha edulis and soft dry wood at different proportions.…”
Section: Introductionmentioning
confidence: 99%